Assessment of genetic diversity among African cassava Manihot esculenta Crantz accessions resistant to the cassava mosaic virus disease using SSR markers - Lokko, Y; Dixon, Alfred G.O.; Offei, S.; Danquah, E.Y.; Fregene, Martin A. (Springer, 2006)
A study was conducted to determine the extent of genetic diversity among African cassava (Manihot esculenta Crantz) accessions resistant to the cassava mosaic virus disease (CMD), using simple sequence repeat (SSR) markers. The accessions included a breeding stock (clone 58308), five improved lines, 62 CMD resistant and 10 CMD susceptible landraces. Genetic diversity was assessed among accessions in five cluster groups derived from UPGMA analysis on data from 18 SSR primer pairs. Average gene diversity, He, was high in all cluster groups, with an average heterozygosity of 0.591 ± 0.061. The estimator of inbreeding Fis revealed a low level of inbreeding within groups and averaged -0.262 ± 0.142. Gene diversity among all accessions was 51.4% and gene diversity within cluster groups was 46.6%, while 4.8% was due to diversity between the different cluster groups. The amount of genetic differentiation measured by Gst and Fst were 9.6% and 12.1% respectively, indicating a weak genetic structure.